2019
DOI: 10.1002/ese3.481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injection parameters on heat extraction performance of supercritical CO2 in enhanced geothermal systems

Abstract: Supercritical CO 2 (SCCO 2 ) is considered as a promising alternative heat extraction fluid in the enhanced geothermal system (EGS) which can reduce atmospheric CO 2 emissions and water waste. However, the heat extraction performance of SCCO 2 is greatly affected by its thermophysical properties, which are high sensitivity to temperature/pressure. In this study, by considering the impacts of temperature and pressure on thermophysical properties of SCCO 2 , a thermo-hydro-mechanical coupling numerical model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…It is found that the net heat extracted by CO 2 increases with the increase of injection pressure in the same amount of time. Comparing with the previous experimental research, the results are generally consistent with the experimental results [37]. The increase of gas injection pressure leads to the increase of gas volume flow in unit time and the heat exchange of gas in rock fracture.…”
Section: Effect Of Injectionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is found that the net heat extracted by CO 2 increases with the increase of injection pressure in the same amount of time. Comparing with the previous experimental research, the results are generally consistent with the experimental results [37]. The increase of gas injection pressure leads to the increase of gas volume flow in unit time and the heat exchange of gas in rock fracture.…”
Section: Effect Of Injectionsupporting
confidence: 90%
“…In the process of CO 2 injection heat recovery, the net heat decreases with the increase of initial temperature of rock sample. Comparing with the previous experimental research, the results are generally consistent with the experimental results [37]. Due to the small size of rock sample, the temperature of 8 Geofluids fracture surface decreases rapidly after fluid injection, resulting in the rapid decrease of initial net heat.…”
Section: Effect Of Initial Temperaturesupporting
confidence: 90%
“…To analyze the relationship between heat transfer conditions and the local roughness of fractures, He et al [17] adopted profile waviness to reflect the local geometric conditions of fractures and recognized that the larger the profile waviness, the smaller the local heat transfer coefficient. Through the study of heat transfer in rough fractures, parameters such as fluid injection velocity, injection temperature, initial temperature of the rock layer, crack width, confinement pressure, and wall roughness all influence the heat transfer mechanisms of fractured reservoirs [18,19]. However, limited by the development of experimental equipment, current research is generally conducted on heat transfer processes at low temperatures with a certain gap from the actual temperatures of HDRs [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Results were obtained regarding changes in reservoir temperature and thermal storage lifespan. Li et al 16 developed a three‐field coupled numerical model to investigate the heat transfer characteristics of ScCO 2 in EGS. They performed sensitivity analysis on various parameters and observed that high injection pressure or low injection temperature would impede heat transfer within the rock mass.…”
Section: Introductionmentioning
confidence: 99%